Clinical features and outcome in 25 dogs with respiratory‐associated pulmonary hypertension treated with sildenafil. (9th December 2019) - Johnson, Lynelle R.; Stern, Joshua A.
Abstract: Background: Pulmonary hypertension (PH) can develop secondary to many common cardiopulmonary diseases, and the use of sildenafil has improved care of affected dogs. Objective: To evaluate response to sildenafil in dogs with respiratory‐associated PH. Animals: Twenty‐five dogs with PH. Methods: Prospective clinical trial. Doppler echocardiography identified dogs with moderate to severe PH, and additional tests were performed to detect underlying diseases. A 17‐point quality of life (QOL) questionnaire was completed, and sildenafil was prescribed, along with other medications deemed necessary for the management of clinically diagnosed respiratory diseases. After 30 days, dogs returned to the hospital for repeat echocardiogram and QOL survey. Results: The median age was 12.4 years, and most dogs were small breed dogs (median weight, 6.5 kg). Syncope (64%), cough (56%), and respiratory difficulty (32%) were the most common presenting complaints. Respiratory diseases associated with PH included tracheobronchomalacia, pulmonary fibrosis, inflammatory airway disease, and brachycephalic syndrome, with multiple diseases in some dogs. Eight of 25 dogs (32%) died or were euthanized within 1 month. In the remaining dogs, tricuspid regurgitation pressure gradient (83.0 ± 17.4 mm Hg before, 55.4 ± 17.4 mm Hg after) and QOL scores were significantly improved after 1 month of sildenafil. Fifty percent mortality was reached 6 months after study entry, with 4 dogs alive 5 years after diagnosis. Conclusions and Clinical Importance: Sildenafil responsiveness is variable in dogs with respiratory‐associated PH, but improved QOL was demonstrated in dogs surviving >1 month, and long‐term survival was noted in some cases.